A new species of Pachyrhabda Meyrick (Lepidoptera: Stathmopodidae) from the Korean Peninsula - Jeong, In-Won; Kim, Sora (Zootaxa, 2024)
The Stathmopodidae, belonging to the Gelechioidea, was first reported by Edward Meyrick in 1913. Since then, species with various morphological characters and various ecological adaptations such as feeding on crops, mosses, and aphids have been reported. In this study, we report the genus Pachyrhabda Meyrick, 1897, for the first time in the Korean Peninsula. This genus of moths is known for consuming spores of ferns. In the present article, we report the discovery of a new species, Pachyrhabda benearena sp. nov. It is diagnosed from the congeneric species by irregular brown spots on the forewings. The new species’ description and geographic distribution information are provided. Additionally, a world checklist of the genus is provided.